2
$\begingroup$

What is the value of:

$$\lim_{n\to\infty}\sqrt{n}\int_0^{1}(1-t^2)^ndt$$

I think I have to use the Theorem of dominated convergence

$\endgroup$
4
  • 1
    $\begingroup$ What have you done so far? People are much more likely to help if they see your dedication to the question. $\endgroup$
    – AlexR
    Oct 16 '13 at 16:51
  • $\begingroup$ Yes, but I wouldn't ask here If I knew how to start... I'm totally lost. $\endgroup$
    – Blanca
    Oct 16 '13 at 16:55
  • $\begingroup$ Have you tried computing the integral? At least for the first few $n$ and maybe even for general $n$? $\endgroup$
    – AlexR
    Oct 16 '13 at 17:01
  • 1
    $\begingroup$ A little partial integration gave me ($A_n$ denoting the integral part) $$A_n = A_{n-1} + \frac{2}{n} \int_0^1 t (1-t^2)^n dt = A_{n-1} + \frac{2}{n(n+1)} A_{n+1}$$ So we have a recurrence relation of $$A_{n+1} = \frac{n(n+1)}{2} (A_n - A_{n-1})$$ $\endgroup$
    – AlexR
    Oct 16 '13 at 17:04
3
$\begingroup$

You can find the value of the limit by squeezing, since: $$\sqrt{n}\int_{0}^{1}(1-t^2)^n dt\leq \sqrt{n}\int_{0}^{1}e^{-nt^2}dt = \int_{0}^{\sqrt{n}}e^{-t^2}dt<\int_{0}^{+\infty}e^{-t^2}dt=\frac{\sqrt{\pi}}{2},$$ and the differences between the first and the second term, the third and the fourth, are $O\left(\frac{1}{\sqrt{n}}\right).$ Through the $t=\cos\theta$ substitution you can also recognize the Wallis product in the LHS.

$\endgroup$
1
  • 1
    $\begingroup$ Perhaps more quickly, you could substitute $t' = t/\sqrt{n}$. $\endgroup$ Oct 16 '13 at 17:19
0
$\begingroup$

From my comment: $$\begin{align*} A_n & = \int_0^1 (1-t^2)^n dt = \int_0^1 (1-t^2)^{n-1} dt - \int_0^1 t^2 (1-t^2)^{n-1} dt \\ & = A_{n-1} - \left( \underbrace{\frac{1}{n} \left[ t^2 (1-t^2)^n \right]_0^1}_{=0} - \frac{2}{n} \int_0^1 t (1-t^2)^n dt \right) \\ & = A_{n-1} + \frac{2}{n} \left( \underbrace{\frac 1 {n+1} \left[ t(1-t^2)^{n+1} \right]_0^1}_{=0} - \frac{1}{n+1} \int_0^1 (1-t^2)^{n+1} \right) \\ & = A_{n-1} - \frac 2 {n(n+1)} A_{n+1} \end{align*}$$ So $$A_{n+1} = \frac{n(n+1)} 2 (A_{n-1} - A_n)$$ With $A_0 = 1, A_1 = \frac{2}{3}$.

Does this get you any further?

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.